Desertos alimentares e a sua espacialização na metrópole de Curitiba, Brasil - Marina Sutile de Lima (Confins)
The article develops the food desert concept under the urban planning perspective and presents three investigations about the spatialization of the food deserts in the metropolis of Curitiba, Brazil. The investigations concern different food deserts aspects, such as the distance between healthy food shops and residences; the proportion of food shops compared to the number of habitants and also to the measure of the area. The results obtained show that the food deserts in the metropolis of Curitiba can be found in the central areas with high income and extensive infrastructure and in the peripheric area as well.